The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/paf.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Findings in Bone Cement Implantation Syndrome–Related Deaths

Abstract: Several mechanisms have been postulated as potentially involved in life-threatening complications during cemented surgery. In this study, we evaluated the role of anaphylaxis and pulmonary fat embolism in the pathophysiology of bone cement implantation syndrome in a series of fatal cases that underwent medicolegal investigations. Postmortem findings in these cases were compared with those obtained from individuals who died after other injuries and/or interventions and in which activated mast cells and pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 40 publications
0
4
0
3
Order By: Relevance
“…Essa síndrome está relacionada a altos índices de morbimortalidade intraoperatória (SINGH et al, 2016). Froidmont et al (2014) realizaram um estudo post-mortem para avaliar o papel da embolia pulmonar e da anafilaxia na fisiopatologia da síndrome da implantação óssea do cimento. Foram analisados 50 indivíduos, desses 6 haviam se submetido a artroplastia total do quadril cimentada e falecidos durante o procedimento cirúrgico, 32 falaceram logo após se submeterem a um acidente de trânsito, 8 após a injeção de contraste e 4 foi a óbito no pós-operatório.…”
Section: Discussionunclassified
“…Essa síndrome está relacionada a altos índices de morbimortalidade intraoperatória (SINGH et al, 2016). Froidmont et al (2014) realizaram um estudo post-mortem para avaliar o papel da embolia pulmonar e da anafilaxia na fisiopatologia da síndrome da implantação óssea do cimento. Foram analisados 50 indivíduos, desses 6 haviam se submetido a artroplastia total do quadril cimentada e falecidos durante o procedimento cirúrgico, 32 falaceram logo após se submeterem a um acidente de trânsito, 8 após a injeção de contraste e 4 foi a óbito no pós-operatório.…”
Section: Discussionunclassified
“…To our knowledge, this is the first study demonstrating the link between the use of bone cement, per se, with intraoperative hemodynamic and/or pulmonary instability and increased postoperative mortality. It has been suggested that the BCIS is caused by an increase in intra-medullary pressure caused by prosthesis insertion and cementation, which will force medullary content into the circulation causing lung embolization (de Froidmont et al 2014). This will, in turn, induce hypoxia, pulmonary vasoconstriction, and an increase in right ventricular (RV) afterload and eventually RV failure with systemic hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review hypothesize the multifactorial model of pathogenesis according to postmortem finding of patient succumbing to intraoperative mortality for the syndrome complex which shows massive pulmonary fat embolism as a major culprit along with mast cell activation [ 9 – 11 ]. Anaphylaxis with release of mediators [ 12 , 13 ] to monomer of bone cement, embolus [ 10 ] has also been proposed giving similar pictures as embolic model. There are also reports of patients requiring intensive care [ 14 ] and succumbing to death postoperatively [ 9 , 15 ] particularly in patients who were unstable in intraoperative periods.…”
Section: Discussionmentioning
confidence: 99%